Natural Resource Dispute Resolution in Majalengka Regency: The Case of Cisambeng Tofu SMEs and the Community - Manulang, Sardjana Orba; Rosmini, Rosmini -; Suyanto, Suyanto -; Sipayung, Baren -; Nurwanty, Iis Isnaeni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Law cannot be separated from the culture of a society because it affects the law. In social life, as human social beings, interaction is a necessity in fulfilling their life needs, however, in fulfilling this life, disputes often occur, including those concerning natural resources. Many disputes and their resolution take place around the world, including in culturally diverse areas. Majalengka Regency, which has developed into an industrial area, is no doubt decorated with various industrial businesses, ranging from MSMEs to large-scale industrial companies, all of which are closely related to environmental problems, including environmental pollution. The research method discussed in this research is socio-legal which examines the culture of the community in the application of alternative dispute resolution over natural resources and the environment. The purpose of this paper is to determine the efficacy of alternative dispute resolution. The results of this study indicate that disputes, especially related to natural resources in the community, can be resolved through consensus deliberation between the parties by prioritizing good faith, as a form of consensus deliberation as a form of local wisdom supported by the government's political will to encourage and ensure all disputes within the community. can be resolved through an alternative dispute resolution (ADR) process and performed its duties properly in this case. Although the effectiveness of ADR was initially lacking, when stakeholders were involved in the mediation process, the dispute resolution process could be carried out properly, as evidenced by the results of initial negotiations and initial mediation, which were less influential.